Pandangan Islam Tentang Kesejahteraan Hidup Ekonomis - Rafi Alfian Hibrizie; Pranata Acun Sandriya; Rizky Fadillah Adrian; M. Backtiar; Yayat Suharyat (Pusat Riset dan Inovasi Nasional, 2023)
One of them is economics in Islam and aims to make people's lives better. The human welfare expressed in the Qur'an alludes to human misery and happiness in this world and in the hereafter. Improvement can be achieved if part of financial independence is considered and good financial management can be recognized in real terms because it creates financial freedom. This exam uses subjective exploration with the help of written research. The consequence of this review, Government Assistance in an Islamic Perspective, is linked to the goals of Islam, particularly the implementation and support of the five basic standards of Maqasid Sharia, all of which lead to a better and just life in this world and the world.